Testing the Radiation Dose Exposure Rate in the CT-Scan Room of Radiology Installation of Private Hospitals in Kudus City - Intan Andriani; Masfufatun Jamil (Jurnal EduHealth, 2023)
According to KEPMENKES RI No. 1014 / MENKES / SK / XI / 2008, radiation exposure measurements in the Radiology Installation room must be carried out periodically at least once a year. In one of the Radiology Installation of private hospitals in Kudus city, the implementation of radiation exposure rate testing of CT-Scan was last done in 2014. The purpose of the study was to determine the procedure for testing the radiation dose exposure rate and the results of testing the radiation dose exposure rate in the CT-Scan room. Data collection methods by means of observation, direct experimentation and documentation. Tests were conducted at 5 points around the CT-Scan room using a surveymeter, each point was measured 3 times. The test results in units of µSv / hour were converted to mSv / year. Furthermore, it was compared with KEPMENKES No.1014 of 2008 regulation that radiation exposure should not exceed the limit of 1 mSv/year. The measurement results of the radiation dose exposure rate at points A, B, D, and E did not leak. The exposure rate value obtained at points A, B, D and E is 0 mSv/year. While the measurement results of the radiation dose exposure rate at point C experienced leakage. The exposure rate value obtained at point C is 1.84 mSv/year.